Alternative treatment methods for bovine mastitis: prospects and limitations (review) - V. D. Zubareva; O. V. Sokolova; M. V. Bytov; A. S. Krivonogova; S. V. Volskaya (Ветеринария сегодня)
Mastitis remains the most common problem of dairy industry despite the preventive measures and treatment schemes being developed. Antibacterial drugs remain first line agents for therapy of the mammary gland inflammatory diseases in animals. Taking into account the risks associated with antibiotic therapy, such as decreased drug effectiveness due to occurrence of bacterial resistant strains, food safety issues, environmental impact and restrictions on the use of antibacterial drugs in veterinary medicine, an increasing number of scientific studies are addressing new therapeutic agents that can serve as an alternative to conventional therapy. The aim of this review is to give an idea of currently available literature data on alternative methods for the prevention and treatment of mastitis in cattle that are not associated with antibiotics. In general, a significant number of in vitro studies aimed at finding new effective and safe drugs are yielding promising results. This review describes the following alternative remedies: probiotics, bacteriocins, bacteriophages, phage enzymes (endolysins), nanoparticles, plant extracts, essential oils and immunobiological agents (vaccines). Understanding the mechanisms of their action will allow recommending the best treatment option for mastitis in each specific case. These treatment methods can potentially reduce use of antibiotics and increase animal productivity, however more in vivo studies are needed to prove the effectiveness of antibiotics used directly in the conditions of farm settings.